Medicinal products, medical devices, or accessories of medical devices: How to qualify gases for spirometry? - Manellari, Sara; Leone, Maria Grazia; Casiraghi, Antonella; Gennari, Chiara Grazia Milena; Minghetti, Paola (Frontiers in Drug Safety and Regulation, 2022)
European legislation provides that each product used for healthcare purposes be regulated according to specific directives and regulations based on its intended use and mechanism of action. However, qualification issues may arise for medical devices, their accessories, and medicinal products. This is the case with gases for spirometry, which support spirometers in measuring patients’ pulmonary capacities. This article discusses criticisms connected to their proper regulatory qualification, detailing why they should be more properly qualified as accessories of medical devices instead of as medicinal products or medical devices.